2021
DOI: 10.1039/d1ra04626h
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of copper selenides with different stoichiometric compositions and their thermoelectric performance at a low temperature range

Abstract: Copper selenides with different stoichiometric compositions were prepared via facile wet-chemistry methods and sintered-Cu2−xSe exhibited the highest ZT value at a low temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Fabrication of bismuth telluride-copper selenide alloys: Bi 2 Te 3 powders (Macklin, 99.9%) were purchased commercially. The copper selenides with different stoichiometric compositions (CuSe, Cu 3 Se 2 and Cu 2−x Se) were prepared by wet chemical methods, which can be seen in our previous article [ 25 ]. Bi 2 Te 3 and copper selenides powders were mixed in an agate mortar, and then fully ground for about 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabrication of bismuth telluride-copper selenide alloys: Bi 2 Te 3 powders (Macklin, 99.9%) were purchased commercially. The copper selenides with different stoichiometric compositions (CuSe, Cu 3 Se 2 and Cu 2−x Se) were prepared by wet chemical methods, which can be seen in our previous article [ 25 ]. Bi 2 Te 3 and copper selenides powders were mixed in an agate mortar, and then fully ground for about 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to bismuth tellurides, copper selenides are another candidate of promising TE materials. It was revealed that the β-phase of Cu 2−x Se exhibits the ideal phonon-glass electron-crystal model, and is also relatively economical and eco-friendly [ 25 , 26 , 27 , 28 ]. More importantly, the very high ZT value, up to 2.3~2.7, of Cu 2 Se-based materials was demonstrated as a characteristic of the p-type TE, due to the optimal carrier concentration and intensive phonon scattering [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric generators (TEGs) are solid-state devices that are made from thermoelectric (TE) materials and can directly realize the conversion between thermal and electrical energy. [9][10][11] Most of the conventional TEGs are rigid, bulky, and heavy, used in applications such as waste heat power generation, refrigeration, and temperature sensing. [12] In recent years, flexible TEGs, which are deformable, light weighted, cost effective, and environmental friendly, have been explored for wearable applications where high deformability and stability are greatly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,21 Copper selenides, anisotropic p-type semiconductor materials, are used in gas sensors, solar cells, and electrochemical energy storage because of their abundance, low cost and high capacity. 16,[22][23][24] Cu 2Àx Se was applied to the anode of SIBs in 2013, and it showed a specic capacity of 120 mA h g À1 aer 100 cycles. 25 To improve the electrochemical performances of copper selenides, downsizing the particle size or compositing with carbonaceous materials could be effective strategies.…”
Section: Introductionmentioning
confidence: 99%